STEGANOGRAFI PADA CITRA BMP 24-BIT MENGGUNAKAN METODE LEAST SIGNIFICANT BIT - David David; A. Murtado; Utin Kasma (STMIK PONTIANAK, 2012)
Abstract : Steganography is the art and science of hiding messages in a message. In the world of modern technology, the secret messages can be hidden behind the image (image), for example. Messages can be encoded in the low-order bits so as not to interfere with media images (image) is displayed. Research Application System Method of Least Significant Bit Steganography aims to provide data security facilities, particularly in terms of hiding data that is intended for corporate, business or personal. The study was based on increased traffic flow data packet delivery via email or other media that directly impact the growing threats and data theft against itself. The research was shaped by the method of experimental study of literature and data collection techniques using literature and documentation. Approach to problem solving using problem identification approach to identify exactly what problems to look for a solution. Design method used is a Rapid Application Development by applying a 5-step design, namely business modeling, data modeling, process modeling, generation and application testing and turnover. The software performs the analysis by comparing the features and the existing criteria and is built using Borland Delphi 7.0 which make the process of concealment and recall data that is hidden as a solution for end-users in terms of the need for data security warnings.Keywords : Data Security, Steganography, Encryption, Decryption, Least Significant Bit (LSB)